PENGARUH KEPEMIMPINAN TRANSAKSIONAL, BUDAYA ORGANISASI, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN - Darmasaputra, I Komang Alan; Sudibya, I Gede AdnyanaI Gede Adnyana (E-Jurnal Manajemen; Vol 8 No 9 (2019)DO - 10.24843/EJMUNUD.2019.v08.i09.p24, 2019)
Ability of leaders in low transactional leadership styles, and unclear organizational culture Difficult to determine by employees, and communication between employees or leaders with employees who are less able to create weak performance of the company. Weakening company performance will have an impact on the achievement of these companies and companies. This study aims to determine the effect of transactional, cultural, and communication on the performance of CV Nusa Kampial employees. This research was conducted at CV Nusa Kampal with 35 employees. Data collection is done by interview method and questionnaire distribution. Data analysis using classical assumption test, multiple linear regression, f test, r square and t test. The results showed that transactional leadership had a significant positive effect on employee performance. Organizational culture had a significant positive effect on employee performance. Stakeholders can improve leadership leadership, organizational culture and good communication so that employee performance continues to increase. The limitations of this study are the lack of samples in the company and only use 3 variables that affect employees, namely transactional leadership, organizational culture and communication. Keywords : employee performance, transactional leadership, organizational culture and  communication